The association of bile acid and thyroid hormone levels in intrahepatic cholestasis of pregnancy - Golbasi, Ceren (2022)
Intrahepatic cholestasis of pregnancy (ICP) leads to adverse perinatal outcomes and these outcomes are affected by high total bile acid (TBA) levels. Studies have shown that thyroid hormones regulate bile acid metabolism. However, few studies have evaluated the role of thyroid hormones in ICP. Objective: To evaluate thyroid function along with TBA levels in ICP. Methods: In this retrospective study, 252 pregnant women, including 126 ICP and 126 controls, were evaluated. Third trimester TBA, thyroid-stimulating hormone (TSH), and free thyroxine (fT4) levels of all pregnant women were assessed. Correlation between TBA and fT4, TSH levels were examined. In addition, the perinatal outcomes of both groups were determined. Results: fT4 levels were significantly higher in ICP. There was also a positive correlation between fT4 and TBA levels. TSH levels were similar in both groups and there was no significant correlation with TBA levels. There was no significant difference between the two groups in thyroid diseases in the third trimester. Conclusions: Higher fT4 level was associated with higher TBA level and fT4 level was associated with higher ICP risk and ICP severity, but TSH level was not associated with higher TBA and higher ICP risk.